Potential impact of climate change on canopy tree species composition of cool‐temperate forests in Japan using a multivariate classification tree model. Issue 2 (16th February 2018) - Matsui, Tetsuya; Nakao, Katsuhiro; Higa, Motoki; Tsuyama, Ikutaro; Kominami, Yuji; Yagihashi, Tsutomu; Koide, Dai; Tanaka, Nobuyuki
Abstract: Climate change will likely change the species composition or abundance of plant communities, and it is important to anticipate these changes to develop climate change adaptation policies. We chose beech ( Fagus crenata Blume) and its competitive tree species as target species to evaluate potential turnover in forest types under climate change using a multivariate classification tree model. To construct the model, geographical presence/absence data for nine target species were used as multivariate response variables, with five climatic factors were used as predictor variables. Current and future distribution probabilities for the target species were calculated, and the 15 dominant forest types were subjectively classified in approximately 1‐km 2 grid cells within the area of the current beech forest distribution. All 16, 398 grid cells of the beech‐dominant forest type (FCR‐QCR) were projected to be replaced in the future by five Quercus crispula ‐dominant types (59% of FCR‐QCR grid cells), four Q. serrata types (22%), two Q. salicina types (8%), or two Abies firma types (0.1%). The FCR‐QCR type remained unchanged (stable) in only 11.4% of grid cells; these were mainly distributed at high elevations in snowy areas on the Sea of Japan side of the country. In contrast, vulnerable habitats (future probability of beech occurrence less than 1.0%) were found at low elevations on both the Sea of Japan and the Pacific Ocean sides. Northwards or upwards range expansions or increases of Quercus spp., in particular, need to be carefully monitored.